2017
DOI: 10.1007/s10620-017-4661-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcomes After Switching from Remicade® to Biosimilar CT-P13 in Inflammatory Bowel Disease

Abstract: BackgroundLimited data are available on long-term clinical outcomes regarding the switch from Remicade® to the infliximab biosimilar CT-P13 in inflammatory bowel disease (IBD) patients.AimsTo investigate long-term efficacy, safety, pharmacokinetic profile, and immunogenicity.MethodsWe performed a single-center prospective observational cohort study following an elective switch from Remicade® to CT-P13 in IBD patients.ResultsEighty-three patients were included (57 Crohn’s disease, 24 ulcerative colitis, and 2 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 20 publications
3
42
2
Order By: Relevance
“…Another prospective study by Smits et al . including 83 IBD patients who switched from infliximab to CT‐P13, also documented that 82% continued CT‐P13 therapy through 1‐year follow‐up without serious adverse events or significant changes in disease activity . Additionally, a prospective study from Spain reported that 83.9% (47/56) of CD and 91.3% (21/23) of UC patients who were in remission at the time of the switch to CT‐P13 from reference infliximab maintained remission at month 6 of therapy .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Another prospective study by Smits et al . including 83 IBD patients who switched from infliximab to CT‐P13, also documented that 82% continued CT‐P13 therapy through 1‐year follow‐up without serious adverse events or significant changes in disease activity . Additionally, a prospective study from Spain reported that 83.9% (47/56) of CD and 91.3% (21/23) of UC patients who were in remission at the time of the switch to CT‐P13 from reference infliximab maintained remission at month 6 of therapy .…”
Section: Discussionmentioning
confidence: 88%
“…32 Another prospective study by Smits et al including 83 IBD patients who switched from infliximab to CT-P13, also documented that 82% continued CT-P13 therapy through 1-year follow-up without serious adverse events or significant changes in disease activity. 33 Additionally, a prospective study from Spain reported that 83.9% (47/56) of CD and 91.3% (21/23) of UC patients who were in remission at the time of the switch to CT-P13 from reference infliximab maintained remission at month 6 of therapy. 18 In line with the results of previous studies, our study showed that a fairly large proportion (44.8% of CD and 42.5% of UC patients) who switched to CT-P13 from its originator continued CT-P13 therapy without disease worsening until the end of follow-up, with a median follow-up of 45 months (IQR 27.0-54.5).…”
Section: Discussionmentioning
confidence: 99%
“…Other prospective studies of CT‐P13 in inflammatory bowel disease patients have been published and provide reassuring results. However, none of these studies, except for a subgroup of one study, directly compared CT‐P13 and RP. In the light of these results, larger and longer‐term studies are needed.…”
Section: Background and Aimsmentioning
confidence: 99%
“…However, none of these studies, [6][7][8][9][10][11] except for a subgroup of one study, 12 directly compared CT-P13 and RP. In the light of these results, larger and longer-term studies are needed.…”
Section: Backg Round and Aimsmentioning
confidence: 99%
“…In from branded IFX (originator) to the IFX biosimilar CT-P13, after which they were followed for 1 year [5]. Both the disease activity, evaluated by Harvey-Bradshaw Index (HBI) for CD and Simple Clinical Colitis Activity Index (SCCAI) for UC and IBD-U, and the inflammatory biomarkers, including C-reactive protein (C-RP) and fecal calprotectin (FCP) did not change during the follow-up year.…”
mentioning
confidence: 99%